Video Game History and the Fact of Blackness - Russworm, TreaAndrea M. (ROMchip, 2019)
Video games studies, including many of our most inspired written accounts of video game history, is very white. Stories about US video game pioneers, from engineers and designers to early adopters and arcade patrons, tend to be mostly about the white men who created, consumed, and periodically saved the industry. Even now that game history is on the verge of becoming as queer and ostensibly nonconformist as some aspects of its games and culture are theorized to be, these new avenues of critical investigation speak most directly to a queer mainstream that has always been constructed as white. Although there is much to be inspired by in the proliferation of emergent video game histories that are more gender-inclusive, trans, or so-called diverse, with few exceptions these progressive accounts still tend to be White. White. White. Black designers, players, blerds, and technocrats have been excluded from the canon of old and new video game histories in much the same way Frantz Fanon theorized that blackness functions as a fact: an outwardly defined pejorative social inscription that justifies its alienation and exclusion.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)